Efeito do sistema endocanabinoide na ação anti-hiperalgésica da gabapentina em modelo animal de dor neuropática induzida por ligadura parcial do nervo isquiático - Buffon, Alexandre Carlos (2017)
Introduction: Neuropathic pain is an important condition whose treatment includes gabapentin (GABAP). The mechanism of analgesic action of GABAP is not fully elucidated. Objective: The present study investigated the contribution of peripheral (plantar) and central (spinal) cannabinoid receptors on the effect of GABAP on the partial sciatic nerve injury (PSNI) model. Methods: Swiss male mice weighing 25-35 g were housed under controlled conditions with free access to food and water and acclimated to the laboratory before testing. PSNI was induced in the anesthetized mice, followed by incision of the right hind limb for nerve exposure, followed by its ligation (1 / 3-1 / 2 of the medial portion) with 8-0 silk thread. In the control group, the nerve was exposed and not connected. The contribution of CB1 and CB2 receptors on the effect of GABAP was evaluated on day 14th after PSNI. Mice received AM281 or AM630 by i.t. (2 μg / 5 μl) or i.pl. (10 g / 20 L) and 15 min after GABAP (30 mg / kg, oral), being evaluated 1 hour after in relation to mechanical hyperalgesia. Data were evaluated by 1 or 2-way ANOVA (Tukey or Bonferroni, respectively, p <0.05). Project approved by CEUA-UNISUL (16.027.5.01.IV). Results: The peripheral treatment with AM281 or AM630 partially reversed (AM281: 47.5  10.6% response; AM630: 40.0  5.3% response) the anti-hyperalgesic effect of GABAP (75.0  11.8% and 67.5  5.3% response, respectively) on the 14th day after the PSNI. With spinal treatment, only AM281 was able to promote this effect (GABAP: 47.5  10.6% and AM281: 82.5  5.9% response). Conclusion: CB1 receptors, at the spinal and peripheral level, as well as CB2 receptors in peripheral level contribute to the anti-hyperlagesic effect of GABAP in this model, and the (*endocanabinoid) EC system can be studied as a target for new treatments for neuropathic pain.